PEMANFAATAN Curcuma longa (L.) OLEH MASYARAKAT LOKAL DI INDONESIA DAN KANDUNGAN METABOLIT SEKUNDERNYA - Dr. Marina Silalahi, M.Si (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2017)
Curcuma longa (L.) is a plant which used by Indonesia ethnic as medicine, dye, and spices. Tulisan ini akan difokuskan pada pemanfaatan kunyit sebagai obat. This article aims to explain the usesand biological activitie of Curcuma longa. This paper is based on literature offline and online media. Off line literatures based on handbooks, dissertations and thesis. Web, Scopus, Pubmed, Journal, and other online media to supplement used in this article. Curcuma longa have been used as medicine for antioxidant, anti bacteria, anti inflamation and antiprotozoa. The C. longa contains curcuminoids: curcumin (diferuloylmethane), demethoxycurcumin, bisdemethoxycurcumin) and volatile oils (tumerone, atlantone, and zingiberone). Keywords: Curcuma longa, curcuminoids, antioxidants, anti inflamations